KACAPING SEBAGAI ALAT MUSIK TRADISIONAL MASYARAKAT SIDRAP: KAJIAN SOSIOMUSIKOLOGI - Andi Ihsan; Andi Taslim Saputra; Khaeruddin Khaeruddin (JURNAL PAKARENA, 2026)
This study aims to map the distribution of Kacaping as a traditional musical instrument of the Bugis people in Sidenreng Rappang (Sidrap) Regency and analyze the socio-cultural relationships that support the sustainability of this musical practice from a socio-musicological perspective. The study uses a qualitative approach with a musical ethnography design. Data were obtained through field observations, in-depth interviews with cultural experts, Kacaping players, and community leaders, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and data verification. The results of the study indicate that Kacaping activities in Sidrap Regency are not evenly distributed, but are concentrated in Tellu Limpoe District, especially Amparita Village, which is currently the center of Kacaping preservation and development. Socio-culturally, Kacaping functions as a symbol of Bugis cultural identity, a medium for transmitting cultural values, and a means of building social relations in the community. The study also found that each player has a different improvisational pattern that forms a personal identity in musical practice. These differences in improvisation indicate that Kacaping is a dynamic cultural practice and continues to undergo a process of cultural construction. Furthermore, Kacaping serves as a cultural arena that brings together performers, cultural figures, craftspeople, and the community in the process of producing meaning, legitimizing culture, and reproducing local knowledge. This finding expands sociomusicological studies by positioning Kacaping not only as a traditional musical instrument, but also as a sociocultural practice that shapes the identity, social relations, and cultural sustainability of the Bugis Sidrap community